Solvent tuned single molecule dual emission in protic solvents: effect of polarity and H-bonding. (28th September 2015) - Chevreux, S.; Allain, C.; Wilbraham, L.; Nakatani, K.; Jacques, P.; Ciofini, I.; Lemercier, G.
Abstract : Phen-PENMe2 has recently been proposed as a promising new molecule displaying solvent-tuned dual emission, highlighting an original and newly-described charge transfer model. The study of the photophysical behaviour of this molecule was extended to include protic solvents. The effects of polarity and hydrogen bonding lead to an even more evident dual emission associated with a large multi-emission band in some solvents like methanol, highlightingPhen-PENMe2 as a promising candidate for white light emission.